(untitled) (Revista Sistemas de Producción Agroecológicos, 2021)
The present work was carried out in a company whose activity is the processing and preservation of fruits, legumes, vegetables and tubers for human consumption, through the dehydration process; This company is located in the city of Villavicencio (Colombia). The objective was to design the Manual of Good Manufacturing Practices (GMP), which comprises a set of guidelines that allows to have a current documentary system based on the requirements of current regulations, to achieve this purpose it was structured as follows : Diagnostic phase by means of a visual inspection of the plant facilities and interviews with the personnel who work in the company, for which a checklist was created based on current regulations, obtaining a compliance percentage of 74%. Based on this result, an action plan was drawn up identifying the non-conformities, evidencing the need for the implementation of a BPM manual. The second phase was the documentary one: Based on the inspection results, the Good Manufacturing Practices Manual was designed, which includes: the sanitation plan, training of food handler personnel and the control system. The third phase was the implementation phase: an implementation plan document was built that allows the company to continuously improve the missing activities and was structured as follows: general objective, proposed tasks, activity schedule and assignment of responsible. Finally, the Manual of Good Manufacturing Practices, the documentation and the implementation plan that were designed, allowed the company to guarantee compliance with the requirements established by national and international regulations, which leads to the elaboration of products in conditions quality and sanitary facilities that meet customer expectations.